2023
DOI: 10.1111/jipb.13410
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid biosynthesis is not from phenylalanine in Arabidopsis

Abstract: The phytohormone salicylic acid (SA) regulates biotic and abiotic stress responses in plants. Two distinct biosynthetic pathways for SA have been well documented in plants: the isochorismate (IC) pathway in the chloroplast and the phenylalanine ammonia-lyase (PAL) pathway in the cytosol. However, there has been no solid evidence that the PAL pathway contributes to SA biosynthesis. Here, we report that feeding Arabidopsis thaliana with Ring-13 C-labeled phenylalanine ( 13 C 6 -Phe) resulted in incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…It is well known that SA plays an important role in the defence response of plants against parasitic pathogens, and powdery mildew is a typical parasitic pathogen. In A. thaliana , about 90% of SA biosynthesis induced by pathogens or UV light is through the ICS pathway (Garcion et al, 2008; Niu et al, 2020; Wildermuth et al, 2001; Wu et al, 2019; Wu et al, 2022). In this study, we found that compared with PM, RL + PM treatment activated the expression of a series of genes in the SA synthesis pathway ( CmICS , CmPBS5 and CmEDS5.1 ) (Figure 2b, Supporting Information: Figure ) and promoted the accumulation of SA (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that SA plays an important role in the defence response of plants against parasitic pathogens, and powdery mildew is a typical parasitic pathogen. In A. thaliana , about 90% of SA biosynthesis induced by pathogens or UV light is through the ICS pathway (Garcion et al, 2008; Niu et al, 2020; Wildermuth et al, 2001; Wu et al, 2019; Wu et al, 2022). In this study, we found that compared with PM, RL + PM treatment activated the expression of a series of genes in the SA synthesis pathway ( CmICS , CmPBS5 and CmEDS5.1 ) (Figure 2b, Supporting Information: Figure ) and promoted the accumulation of SA (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…S1 B). However, Wu et al [ 13 ] recently found that phenylalanine could not synthesize SA (2-Hydroxybenzoic acid, 2-HBA), but synthesized 4-hydroxybenzoic acid (4-HBA), an isomer of SA. In this study, several DEGs were associated with signaling pathways such as JA/ethylene, SA, auxin, abscisic acid (ABA), and cytokinin (CTK), and JA may play a key role via negative regulation of α-linolenic acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The means by which the PAL pathway promotes SA synthesis is still controversial. A recent study indicated that the PAL gene catalyzes phenylalanine to finally synthesize 4-hydroxybenzoic acid (4-HBA) rather than SA [ 30 ]. In any case, it is clear that BA is the precursor of SA.…”
Section: Sa Biosynthesis In Plantsmentioning
confidence: 99%